Perception and behaviour on blood glucose control among diabetic patient in Kuantan district, Pahang on 1997 - Adibah Hani Haron; Md. Idris Mohd Nor (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Diabetes Mellitus is among the leading cause of mortality and morbidity in Malaysia and in other industrialized countries allover the world. Changing life styles has been implicated as the main cause of this disease. A prevalence study has been conducted in Kuantan Hospital and six health clinics in February 1997. The purpose of the study is to identify the perception and behaviour of diabetic patient on blood glucose control. This research is also looking at the relationship between blood glucose control and other risk factors including age, race, sex, income, marital status, type of occupation, degree of easiness to get treatment and duration of disease with the hypothesis that blood glucose control is associated to those factors mentioned. All diabetic patient who came to get treatment from hospital and health clinics at the f' outpatient department were selected for the study. Criteria used for categorization patients into good and poor control are history of ketoacidosis, examination of urine glucose (in the clinic and house) and follow the date given by medical staff when r: getting diabetic treatment. Total of three hundred respondents were recruited in this research. The results shown that 89 patients (29.7%) were categorised into good blood r glucose control. Blood glucose control is significantly associated with marital status f (p